KUALITAS PELAYANAN PROGRAM JAMKESMAS DAN JAMKESDA DI RSUD PROF.DR. MARGONO SOEKARJO PURWOKERTO KABUPATEN BANYUMAS - Dwi Agung Subiyantara; Wiwik Widayati; Ahmad Taufiq (Journal of Politic and Government Studies, 2013)
Jamkesda Jamkesmas health program and a health program for the poor people afford the government. But in Indonesia there is the fact that they are often discriminated against and got poor service even if the payment is guaranteed by the government. Found many gov-ernment hospitals provide services that are not fair to the participants Jamkesmas and Jam-kesda. Based on the background of the researchers interested in examining the quality care of Jamkesmas and Jamkesda in RSUD Prof. Dr. Margono Soekarjo Purwokerto Kabupaten Banyumas Central Java Provincial Government owned.The research method used in this study is a qualitative method. The data in this study come from interviews with respondents and the data obtained from these reports, books, jour-nals, magazines, and so on. The data was then compiled with the stages of examining the data obtained from the field, analyzing the data and information and then draw conclusions and verification. Thus generating descriptive data to portray the quality of services and programs Jamkesmas Jamkesda Hospital Prof. Dr. Margono Soekarjo Navan.In this research it was found since 2011 the government launched the program Jam-persal and treatment of Thalassaemia Major as one of the tangible evidence of improved quality of care Jamkesmas, while Jamkesda not. Cause groove referral patterns that do not work well due to the lack of clear regulations regarding patient referral grouping and no so-cialization about it. The government is not transparent about the data base Jamkesmas and Jamkesda participants. Special Jamkesda, Central Java Provincial Government and Regency/City Government lacks transparency regarding the availability of funds for participants Jam-kesda claims and a weak distribution system because it is only through an agreement. How-ever, the Hospital Prof. Dr. Margono Soekarjo able to be professional in providing services Jamkesmas or Jamkesda and do not discriminate. Terms administration service that is easy to understand, clearly, not berbelli the bush, cleanliness is always awake, officers were friendly and tolerant, and sophisticated equipment is a testament to the quality of service in hospitals Jamkesmas and Jamkesda Prof. Dr. Margono Soekarjo.The conclusion of this research is Jamkesmas servicesSome regency/city in Central Java providing health facilities vary in Jamkesda. These3programs should apply to the whole people of Indonesia if it holds the principle of justice. Recommendation in this research is the Government needs to empower the participants Jam-kesmas or Jamkesda regarding referral patterns is good and true healthy living to the partici-pants Jamkesmas and Jamkesda be more concerned because it can reduce the cost of claims and considering high occupancy room space for class III participants Jamkesmas and Jam-kesda.Keywords : Jamkesmas, Jamkesda, Government Hospital